Nevus Lipomatosus Cutaneous Superficialis - A Rare Hamartoma: Report of Two Cases - Mayank Goyal (Journal of Clinical and Diagnostic Research, 2016)
Nevus Lipomatosus Cutaneous Superficialis (NLCS) is a rare benign hamartomatous disorder in which mature collection of adipocytes are present ectopically in the dermis. NLCS usually presents as multiple, soft, pedunculated, cerebriform, yellowish or skin colored papules, nodules, or plaques, mostly involving the pelvic or gluteal region. We herewith report two cases of adult onset classical NLCS. First case had a classical presentation with lesion on lower back while second case was associated with some unusual features like occurrence on pubic area and associated comedo-like lesions.